2014
DOI: 10.1111/grow.12051
|View full text |Cite
|
Sign up to set email alerts
|

Local and Global Geographies of Innovation: Structures, Processes, and Geographical Contexts from a Firm Perspective

Abstract: This paper introduces a special issue addressing the relationship between innovations and geographical contexts. The content, role, and sourcing of knowledge and how this relates to production systems and particular innovation projects is addressed. It includes a discussion about how firm strategies and organizational arrangements such as sourcing strategies, brokering arrangements, and project bundling effects the position of clusters as a knowledge source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In essence, this new stream of research has caused a conceptual shift from a research focus on innovative territories to a time-spatial analysis of innovative processes (see several recent special issues, e.g. in Growth and Change on “Geographies of Innovation and Production Systems” (Rusten and Overå, 2014), in Geoforum on “From Cluster to Process” (Ibert et al, 2015) and in Regional Studies on “From ‘TIMs’ to ‘Territorial Knowledge Dynamics’ (Jeannerat and Crevoisier, 2016)).…”
Section: The Conceptual Basis Of Open Regionmentioning
confidence: 99%
“…In essence, this new stream of research has caused a conceptual shift from a research focus on innovative territories to a time-spatial analysis of innovative processes (see several recent special issues, e.g. in Growth and Change on “Geographies of Innovation and Production Systems” (Rusten and Overå, 2014), in Geoforum on “From Cluster to Process” (Ibert et al, 2015) and in Regional Studies on “From ‘TIMs’ to ‘Territorial Knowledge Dynamics’ (Jeannerat and Crevoisier, 2016)).…”
Section: The Conceptual Basis Of Open Regionmentioning
confidence: 99%
“…In this way, it can be observed that the commitment of companies that have a high level of sense of belonging to their district results in a higher level of confidence in their relations with district agents. In this respect, several studies have underlined that the sense of belonging among the agents of a district facilitates understanding and mutual trust (Cotic-Svetina, Jaklic, & Prodan, 2008;Fazio & Lavecchia, 2013;Roskruge et al, 2012;Rusten & Overå, 2014). Thus, districts are a favorable context for the development of trust since the common identity typical of the sense of belonging offers the key confidence between agglomerated firms needed to attract new resources (Staber & Sautter, 2011).…”
Section: Influence Of Sense Of Belonging On Relational Trustmentioning
confidence: 99%
“…Tödtling and Trippl (2005) argue that innovation policy must be differentiated on the basis of the region type (central, peripheral, old industrial) it is targeting. Research experience from the Hordaland region (where Mongstad is located) and other regions in Norway also point to the need to better adjust policy instruments to industry type and to firms' structural composition and innovation capacity (Rusten and Overå, 2014). Finally, the RIS literature tends to focus on knowledge and technology intensive industries, whose inertia and path dependencies are primarily related to human resources, competence and market positions (Malerba, 2010).…”
Section: Theoretical Background and Frameworkmentioning
confidence: 99%